ICU acquired weakness or something else? - Acharya, Subhash; Koirala, Sabin; Shrestha, Anjan; Aryal, Diptesh (Journal of Society of Anesthesiologists of Nepal, 2015)
An elderly female presented to Intensive Care Unit with generalized weakness and altered sensorium with past history of adenocarcinoma of larynx. She was managed with Radiation Therapy and Chemotherapy in the past. Current admission to the intensive care unit was for aspiration pneumonitis and respiratory failure requiring mechanical ventilation. She then progressively developed muscle weakness, which was provisionally diagnosed and managed as critical illness polyneuromyopathy (ICU acquired weakness) and muscle biopsy was sent, as there were no obvious neurological signs and she was not recovering from her muscle weakness as well. She then developed Catheter related sepsis and refractory septic shock, and then she passed away. Her muscle biopsy report that was available postmortem revealed that she had severe toxoplasma infestation that remained in shadow. Journal of Society of Anesthesiologists of Nepal 2015; 2(1): 25-27